2007
DOI: 10.1007/s11207-007-0046-8
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Chromosphere in a Coronal Hole

Abstract: We study the Ca II K, H, and λ 849.8 nm line profiles in two regions of the quiet Sun, one being located in the extensive low-latitude coronal hole observed on 3 through 5 August 2003, and the other being located outside the coronal hole. Comparison of the profiles was carried out separately for cells and cell boundaries of the chromospheric network. Our principal result is that space-and time-averaged profiles of the central self-reversal in the coronal hole sites differ from those outside of the hole: Intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Coronal holes are more or less indistinguishable from their surroundings in the photosphere and low chromosphere, and usually one cannot see any significant intensity contrast between hole and non-hole regions until the temperature exceeds about 10 5 K. Spectra, however, can help make the distinction clearer. Teplitskaya et al ( 2007 ) found that central self-reversals in the chromospheric Ca ii H and K lines are noticeably different in coronal holes as opposed to surrounding quiet-Sun regions. A frequently used observational diagnostic of coronal hole boundaries is the He i 10830 Å near-infrared absorption line triplet (Harvey et al , 1975 ; Harvey and Recely, 2002 ).…”
Section: Properties Of On-disk Coronal Holesmentioning
confidence: 99%
“…Coronal holes are more or less indistinguishable from their surroundings in the photosphere and low chromosphere, and usually one cannot see any significant intensity contrast between hole and non-hole regions until the temperature exceeds about 10 5 K. Spectra, however, can help make the distinction clearer. Teplitskaya et al ( 2007 ) found that central self-reversals in the chromospheric Ca ii H and K lines are noticeably different in coronal holes as opposed to surrounding quiet-Sun regions. A frequently used observational diagnostic of coronal hole boundaries is the He i 10830 Å near-infrared absorption line triplet (Harvey et al , 1975 ; Harvey and Recely, 2002 ).…”
Section: Properties Of On-disk Coronal Holesmentioning
confidence: 99%
“…The sources of the solar wind are located at the heights of the chromosphere and transition zone (Marsch, 2018), and yet most research on coronal holes is concerned only with their manifestations and characteristics in the upper atmosphere (e.g. Banerjee et al, , 2020Banerjee, Pérez-Suárez, and Doyle, 2009;Banerjee, 2010;Banerjee, Gupta, and Teriaca, 2011;Krishna Prasad, Banerjee, and Van Doorsselaere, 2014), while works studying the lower atmosphere under coronal holes have not been as numerous in the last decade (Kobanov, Makarchik, and Sklyar, 2003;De Pontieu et al, 2007;Teplitskaya, Turova, and Ozhogina, 2007;Kobanov and Sklyar, 2007;Teplitskaya, Turova, and Ozhogina, 2010;Tian et al, 2014b;Zubkova et al, 2014;Grigoryeva, Turova, and Ozhogina, 2016). With this article, we try to contribute to this field by analyzing the oscillations we observe in the lower atmosphere under two coronal holes.…”
Section: Introductionmentioning
confidence: 99%
“…Sources of the solar wind are located at the heights of the chromosphere and the transition zone (Marsch 2018), and yet most of the research on coronal holes concerns only their manifestations and characteristics in the upper atmosphere (e.g. Banerjee et al 2009bBanerjee et al , 2020Banerjee et al , 2009aBanerjee 2010;Banerjee et al 2011;Krishna Prasad et al 2014), while the works studying the lower atmosphere under coronal holes have not been as numerous in the recent decade (Kobanov et al 2003;De Pontieu et al 2007;Teplitskaya et al 2007;Kobanov & Sklyar 2007;Teplitskaya et al 2010;Tian et al 2014a;Zubkova et al 2014;Grigoryeva et al 2016). With this article, we try to contribute to this area by analyzing the oscillations that we observe in the lower atmosphere under two coronal holes.…”
Section: Introductionmentioning
confidence: 99%